Changing Characteristics of Pharmaceutical Prices in China Under Centralized Procurement Policy: A Multi-Intervention Interrupted Time Series - Long, Hongfei; Yang, Ying; Geng, Xin; Mao, Zongfu; Mao, Zhenhua (Frontiers in Pharmacology, 2022)
Objective: National centralized drug procurement organized by the Chinese government currently represents the largest group purchasing organization worldwide, to establish a reasonable price formation mechanism. This study aimed to evaluate the effects of centralized procurement policy on drug price and price ratio in China. Method: Monthly drug procurement data of public medical institutions were extracted from the national procurement database, including 11 pilot cities and 36 months from January 2018 to December 2020. Centralized procured INNs (International Nonproprietary Names) (n=25) and their alternative INNs (n=96) were selected as study samples. Centralized procured INNs were divided into bid-winning and non-winning products according to the bidding results. Drug price, price distribution, and price ratio were measured. Multi-intervention interrupted time series analysis was performed to estimate the policy impacts in two centralized procurement periods. Results: The price of centralized procured INNs showed an immediate drop of 44.57% (β=-0.59, p<0.001) at the policy implementation, among which bid-winning drugs decreased by 61.71% (β=-0.96, p<0.001). No significant change in the price level or trends was found for non-winning products and alternative drugs in the first-year procurement period (all p-values>0.05). During the second-year procurement period, alternative drugs in four therapeutic categories detected significant increases in the price level (all p-values<0.05). The overall coefficient of variation of price distribution exhibited upward trends after policy implementation. Among most centralized procured INNs, the price ratio between certificated generics (generics that have passed the consistency evaluation) and original drugs declined significantly after policy intervention (p<0.05), while the price ratio between uncertificated and certificated generics increased significantly (p<0.05). Conclusion: Chinese government-organized group purchasing resulted in prominent price reduction of bid-winning drugs. The policy observed a short-term “spillover” effect of synergistic price reduction, while the effect wore off after one-year procurement period. The extremely dispersed price distribution, as well as unreasonable price ratios, requires further effective price regulation means.